Heart failure with preserved ejection fraction or non-cardiac dyspnea in paroxysmal atrial fibrillation: The role of left atrial strain. (15th January 2021) - Katbeh, A.; De Potter, T.; Geelen, P.; Di Gioia, G.; Kodeboina, M.; Balogh, Z.; Albano, M.; Vanderheyden, M.; Bartunek, J.; Barbato, E.; Van Camp, G.; Penicka, M.
Abstract: Background: Diagnosis of heart failure with preserved ejection fraction (HFpEF) in patients with dyspnea and paroxysmal atrial fibrillation (AF) is challenging. Speckle tracking-derived left atrial strain (LAS) provides an accurate estimate of left ventricular (LV) filling pressures and left atrial (LA) phasic function. However, data on clinical utility of LAS in patients with dyspnea and AF are scarce. Objective: To assess relationship between the LAS and the probability of HFpEF in patients with dyspnea and paroxysmal AF. Methods: The study included 205 consecutive patients (62 ± 10 years, 58% males) with dyspnea (NYHA≥II), paroxysmal AF and preserved LV ejection fraction (≥50%), who underwent speckle tracking echocardiography during sinus rhythm. Probability of HFpEF was estimated using H2 FPEF and HFA-PEFF scores, which combine clinical characteristics, echocardiographic parameters and natriuretic peptides. Results: Patients with high probability of HFpEF were significantly older, had higher body mass index, NT-proBNP, E/e', pulmonary artery pressure and larger LA volume index than patients in low-to-intermediate probability groups (all p  < 0.05). All components of LAS and LA strain rate showed proportional impairment with increasing probability of HFpEF (all p  < 0.05). Out of the speckle tracking-derived parameters, reservoir LAS showed the largest area under the curve (AUC = 0.78, p  < 0.001) and the strongest independent predictive value (OR: 1.22, 95% CI 1.08–1.38) to identify patients with high probability of HFpEF. Conclusions: Reservoir LAS shows a high diagnostic performance to distinguish HFpEF from non-cardiac causes of dyspnea in symptomatic patients with paroxysmal AF. Highlights: LA strain showed to be a useful index to diagnose HFpEF in patients with history of AF. LA strain might provide additional clue for diagnosing HFpEF in patients with intermediate probability of HFpEF. Monitoring atrial function in this clinical setting might provide useful prognostic information.